A126 REAL WORLD CLINICAL EFFICACY OF LOW DOSE USTEKINUMAB INDUCTION IN CROHN'S PATIENTS REFRACTORY TO ANTI-TNF THERAPY. (1st March 2018) - AL YATAMA, N; ROFAIEL, R; Chande, N; Ponich, T; Gregor, J C
Abstract: Background: Patients with moderate to severe Crohn's disease refractory or intolerant to steroids, immunomodulators and anti-TNF therapy currently have few options for medical management outside of clinical trials. Ustekinumab, a monoclonal antibody, which inhibits interleukins 12 and 23 is currently being used safely and effectively to treat patients with psoriasis and recent studies suggest that it may be of value in treating moderate to severe Crohn's disease in patients both naive and refractory to anti-TNF therapy. Currently the intravenous formulation of ustekinumab used in these studies is unavailable for use outside of clinical trials. Aims: The aim of this study was to examine the clinical efficacy of subcutaneously (sc) loaded ustekinumab in patients with moderate to severe Crohn's disease who had failed at least one anti-TNF agent. Methods: All patients given a loading dose of ustekinumab 270 mg sc over two weeks were included in this retrospective analysis. Baseline demographic data was collected. The primary outcome was the proportion of patients who achieved a Harvey-Bradshaw Index (HBI) </= 3 and who remained on ustekinumab at six months of therapy post loading dose, without requiring a change in ustekinumab dose nor the addition of any new agents to treat their Crohn's disease. Secondary outcome measures included the number of patients with serious adverse effects, the proportion of patents judged as improved (reduction of their HBI but not meeting the target of 3 or less) and the proportion of patients with a HBI </=3 regardless of whether or not their Crohn's medications were increased. Results: 47 patients were started on sc ustekinumab, among which 30 (64%) were females. The age of patients ranged from 24 to 74 years old with a mean of 46.1 years of age. Twenty eight (60%) had failed two anti-TNF agents while the remainder had failed only one. The mean HBI at drug initiation was 9.7 (range 5 to 16). All patients were still on ustekinumab at six months with 2 patients (4 %) every 12 weeks, 43 patients (92%) every 8 weeks, 1 patient (2%) every 6 weeks, and 1 patient (2%) every 4 weeks). At six month follow up 24/47 patients (51%) had an improvement in HBI of at least 3 points and 10/47 (21%) met the primary outcome measure of HBI 3 or less. No serious adverse events (ie. infection, systemic allergic reactions or malignancies) were observed. Conclusions: Loading doses of ustekinumab 270 mg sc administered over a two week period followed by maintenance doses at 4 or 12 week intervals appear to be clinically efficacious in the treatment of patients with moderate to severe Crohn's disease refractory to anti-TNF therapy. With further experience it will be determined whether higher loading and maintenance doses given either sc or intravenously will further improve the rates of response and remission. Funding Agencies: None